2005
DOI: 10.1080/09546630500283664
|View full text |Cite
|
Sign up to set email alerts
|

An open study to determine the efficacy of blue light in the treatment of mild to moderate acne

Abstract: Eight 10- or 20-minute treatments over 4 weeks with a narrowband blue light was found to be effective in reducing the number of inflamed lesions in subjects with mild to moderate acne. The treatment had little effect on the number of comedones. The onset of the effect was observable at the first assessment, at week 5, and maximal between weeks 8 and 12. Blue light phototherapy using a narrowband LED light source appears to be a safe and effective additional therapy for mild to moderate acne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 16 publications
5
59
1
Order By: Relevance
“…This tendency might be caused by the fact that P. acnes, the main target of light therapy, resides mostly in inflammatory acne lesions [51]. The mean percentage improvement of inflammatory lesions was similar to that of Papageorgiou's study [24] where the mixture of blue and red light was used (76%), but higher than those where blue light was used alone such as Gold et al [31] (36%), Elman et al [27] (59-67%), Morton et al [30] (64%), Kawada et al [26] (papule:69.3%, pustules: 73.3%), and Tzung et al [28] (approximately 60% improvement in papulopustular lesions and 20% aggravation in nodulocystic lesions, exact numerical data not provided). It was notable that the nodulocystic lesions responded to our treatment as well, whereas they were aggravated in Tzung's study [28] where blue light was used alone.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…This tendency might be caused by the fact that P. acnes, the main target of light therapy, resides mostly in inflammatory acne lesions [51]. The mean percentage improvement of inflammatory lesions was similar to that of Papageorgiou's study [24] where the mixture of blue and red light was used (76%), but higher than those where blue light was used alone such as Gold et al [31] (36%), Elman et al [27] (59-67%), Morton et al [30] (64%), Kawada et al [26] (papule:69.3%, pustules: 73.3%), and Tzung et al [28] (approximately 60% improvement in papulopustular lesions and 20% aggravation in nodulocystic lesions, exact numerical data not provided). It was notable that the nodulocystic lesions responded to our treatment as well, whereas they were aggravated in Tzung's study [28] where blue light was used alone.…”
Section: Discussionsupporting
confidence: 60%
“…In addition to the wound healing enhancement, photorejuvenation, which refers to the process where light is used to improve photoaged skin, has been proposed as another application of LED by Weiss et al [46][47][48][49] (590 nm) and Russell et al [50] (633 and 830 nm). The use of blue LEDs in the treatment of acne was reported by Morton et al [30], which showed a good treatment effect on inflammatory acne lesions. Although the exact mechanisms of action have not yet been clarified, LEDs are considered to be highly effective in enhancing cellular activities through mitochondrial photobiomodulation (visible red waveband) as well as in eliciting the photodynamic destruction of P. acnes (visible blue waveband) [30,45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations